Delayed perforation of the sigmoid colon after endoscopic reduction of sigmoid volvulus. Issue 3 (21st November 2014) - Ohtsuka, Yasuhiro; Tsuchiya, Shin; Shida, Takashi; Komatsu, Teisuke
Abstract : Case: An 81‐year‐old woman was diagnosed with sigmoid volvulus. As there were no signs of peritoneal irritation, emergency endoscopic reduction was attempted and achieved successfully. Although she remained stable on the following day, she suddenly developed perforative pan‐peritonitis 35 h after the procedure. Outcome: Emergency laparotomy revealed a 10‐mm‐diameter perforation at the anti‐mesenteric wall of the top of the sigmoid loop, and sigmoid resection with Hartmann's procedure was carried out. Pathological examination revealed ischemic necrosis around the perforation site. She recovered well with intensive care, and was discharged 32 days later. Conclusion: Delayed sigmoid perforation after endoscopic reduction of sigmoid volvulus is a rare but important and life‐threatening pitfall, and should always be considered by acute care physicians. To prevent this dangerous complication, evaluation of the viability of the entire sigmoid by direct vision and semi‐emergency operation as soon as the patient's condition is optimized after endoscopic reduction may be essential.